PENGARUH PEMBERIAN JUS TOMAT (LYCOPERSICUM COMMUNE) TERHADAP TEKANAN DARAH WANITA POSTMENOPAUSE HIPERTENSIF - Lestari, Aryati Puji; Rahayuningsih, Hesti Murwani (Journal of Nutrition College, 2012)
ABSTRACT Background: Hypertension is the third leading cause of death in Indonesia reached 6.7% of the population mortality at all ages. The blood pressure of postmenopausal women tends to increase due to decreased of the protective effect of estrogens and increased of salt sensitivity. Tomato fruit (Lycopersicum commune) contains potassium and lycopene which has the effect of decreasing blood pressure.Objective: Determine the effect of consuming tomato juice (Lycopersicum commune) to the blood pressure of hypertensive postmenopausal women.Method: This study is an experiment with a pre-post test control group design. The numbers of study subjects are 34 respondents with systolic blood pressure ≥ 140 mmHg and or diastolic ≥ 90mmHg. The tomato juice of 200 ml consumption once a day for 7 days is made from 150 gram tomato, 5 gram sugar, and 50 ml water.Result: There is a decrease in systolic blood pressure of 11.76 ± 7.276 mmHg and diastolic blood pressure of  8.82 ± 3.321 mmHg in the treatment group. The tomato juice consumption significantly influences the decrease in systolic blood pressure and diastolic blood pressure.Conclusion: The tomato juice significantly decreases the systolic and diastolic blood pressures in postmenopausal hypertensive women.Keywords: tomato juice, blood pressure, hypertension